Local administrations in life long learning and music education in the context of art education - CAN, AJDA AYLİN (ELSEVIER SCIENCE BV, 2011)
Today, all aspects of education have started to be discussed in line with the concept of life long learning (LLL). Regarding the field, social service and education studies gained importance in local administrations and studies that are aimed at music education were constituted in the context of art education. The Children's Art Center (CAC) of Istanbul Kadikoy Municipality is an exemplary institution for such studies. This study investigated the facilities of the center, teachers' views about the facilities that are provided for the principles and objectives of LLL in the field of music, knowledge of teachers regarding LLL and the current situation concerning their current and planned activities. As a consequence, the importance of the contribution of the teacher with knowledge and extensification of similar centers for children's music education were expressed in line with the objectives and principles of the process of LLL. (C) 2011 Published by Elsevier Ltd.
Keywords: Life long learning; local administration; municipality; art education; music education